Addressing nodal constraints on the capacity of railways. (May 2017) - Armstrong, John; Preston, John; Potts, Chris; Bektas, Tolga; Paraskevopoulos, Dimitris
As the demand for passenger and freight transport on Britain's railways increases, providing additional capacity and making the best use of the existing infrastructure are priorities for the industry. Since the stations and junctions forming the nodes of the railway network tend to form the constraints on route and network capacity, improved understanding of their operation and capacity characteristics is particularly important. This paper describes the research undertaken to improve the understanding of nodal capacity and capacity utilisation, and to route and schedule trains more efficiently through nodes, thus improving service quality and/or releasing capacity for additional train services.